(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
Onychomycosis is the fungal infection of nails caused by dermatophytes, nondermatophyte molds, and yeasts. Onychomycosis is the most common nail disease with the prevalence of 5.5% all over the world. Objective to know the types of fungi that particularly affect the nail area in men and women. Methods. About 25 nail samples were collected, including 13 males and 12 females. These samples were then grown on SDA and DMT medium and incubated at 37 degrees for a period of 2-14 weeks. After that, the samples were diagnosed using dissecting microscope .Results .The percentage of positive samples was (76%) while the percentage of negative samples was (24%).where different species of fungi appeared in both females and males, such as Cladosporium sp. ,Aspergillus sp. ,Chaetomiums sp. and Penicillium sp. .Conclusions . the prevalence rate of onychomycosis in males was higher than in females.